The economic and clinical burden of early versus late initiation of celecoxib among patients with osteoarthritis - Shelbaya A; Solem CT; Walker C; Wan Y; Johnson C; Cappelleri JC (Dove Medical Press, 2018)
Ahmed Shelbaya,1,2 Caitlyn T Solem,3 Chris Walker,4 Yin Wan,3 Courtney Johnson,3 Joseph C Cappelleri1 1Pfizer Inc., New York, NY, 2Columbia School of Public Health, New York, NY, 3Pharmerit International, Bethesda, MD, USA; 4Pfizer Ltd., Tadworth, Surrey, UK Objective: This study aimed to evaluate the characteristics associated with early versus late initiation of celecoxib treatment after osteoarthritis (OA) diagnosis and whether economic and safety outcomes differ between patients with early versus late initiation of celecoxib.Methods: Adults (≥18 years) with a confirmed OA diagnosis (International Classification of Diseases, 9th Edition, Clinical Modifications code: 715.XX), ≥12 months of continuous pre- and post-index enrollment, and ≥1 post-index claim for celecoxib were included from the MarketScan® Commercial Claims and Encounter Database (2009–2013). Index date was defined as initial OA diagnosis. Patients were categorized as initiating celecoxib early (within 6 months of index date) or late (≥6 months after index date). Logistic regressions were used to assess characteristics associated with early versus late celecoxib initiation. Key outcomes included health care resource utilization (HCRU) and costs post-index, and adverse event incidence post-celecoxib initiation. Unadjusted and adjusted comparisons (using generalized linear models with a gamma distribution for costs and Poisson distribution for event and resource utilization) were made between early and late celecoxib initiators.Results: Of the 62,434 OA patients identified, 27,402 were early and 35,032 were late initiators. Post-index hospital admissions and length of stay did not differ statistically between early versus late initiators after controlling for pre-index event rates and covariates, but early patients had significantly fewer outpatient (incidence rate ratio [IRR]: 0.96; 95% confidence interval [CI]: 0.95, 0.97) and emergency room visits (IRR: 0.89; 95% CI: 0.84, 0.95). After adjustment for key covariates, early initiators (versus late initiators) had lower all-cause (US$12,909 versus US$13,781, P<0.001) and OA-related (US$4,988 versus US$5,178, P=0.015) costs per person-year. Early initiators had no statistically significant difference in the incidence of post-celecoxib cardiovascular (IRR: 0.92; 95% CI: 0.73, 1.14), gastrointestinal (IRR: 1.25; 95% CI: 0.81, 1.92), or renal (IRR: 1.19; 95% CI: 0.65, 2.18) events, controlling for pre-index event rates and covariates when compared to late initiators.Conclusion: In this real-world cohort, patients initiated on celecoxib early (versus late) had significantly lower costs and HCRU; this may warrant consideration when making treatment decisions for OA patients. Keywords: osteoarthritis, celecoxib, nonsteroidal anti-inflammatory drug, economic burden, health care resource use